Key features of magnesium that underpin its role as the major ion for electrophilic biocatalysis. (23rd April 2020) - Gottesman, Max E.; Chudaev, Maxim; Mustaev, Arkady
Abstract : To investigate divalent metal ion (Me 2+ ) requirements in electrophilic biocatalysis, we compared Mg 2+, Mn 2+, Co 2+, Zn 2+, Cu 2+, Ni 2+, Cd 2+, Ca 2+, and Fe 2+ activities with 13 enzymes executing nucleotidyl and/or phosphoryl transfer. We find that each Me 2+ ion was highly catalytically active with one or more of the related enzymes. This result suggests that features of Me 2+ coordination at the active center, and/or the enzyme‐mediated presentation of the reactants to the chelated Me 2+, rather than the nature of the Me 2+, determine the ability of the Me 2+ to support catalysis. At physiological pH, all the tested Me 2+ ions, with the exception of Mg 2+, produced insoluble complexes with inorganic phosphate (Pi ) and bicarbonate ( HCO 3 - ). These data suggest that early in the development of life, bioavailability and biocompatibility with these abundant cellular metabolites may have been decisive factors in the choice of Mg 2+ as the major ion for biocatalysis. Taking into account the concentrations of inorganic ions in the ancient environment in which the first cells emerged, as inferred from the 'chemistry conservation principle', the choice of Mg 2+ was predetermined prior to the origin of life. Abstract : The features of Me 2+ coordination at the active center, rather than the nature of the Me 2+, determine the ability of the Me 2+ to support biocatalysis. All the tested Me 2+ ions, with the exception of Mg 2+, produced insoluble complexes with inorganic phosphate and bicarbonate, suggesting that bioavailability and biocompatibility with these abundant cellular metabolites may have been decisive factors in the choice of Mg 2+ as major ion for biocatalysis.